Resistensi Perempuan terhadap Victim Blaming dalam Kekerasan Seksual pada Cerpen “Perempuan, Perempuan, Turunkan Rambutmu” - Marta Widyawati (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
Sexual violence against women followed by victim blaming is still common in Indonesia. This is based on the existence of a strong male domination structure that makes it difficult for women to position themselves. This study aims to analyze the forms of sexual violence and victim blaming, and to interpret the resistance that emerged from women to this in the short story